RESULTS OF PRICES SURVEY FOR MANUFACTURERS OF BANK INDONESIA WORKING AREA LHOKSEUMAWE - Khaddafi, Muammar; Heikal, Mohd.; Nur Ilham, Rico; Falahuddin, Falahuddin; Arliansyah, Arliansyah; Munandar, Munandar; Fuadi, Fuadi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
Report Survey Price Producer made in skeleton support Bank Indonesia (BI) in updating Data Center Information Price Food Strategic (PIHPS) which is something center information that contains price of 10 commodities food strategic goals monitoring price, coordination policy as well as means for expand access information for society . Report activity survey this containing about results activity survey conducted against 7 commodities main dominant inflation along with quality from commodity that. Surveyed area is scope region The work of the Lhokseumawe Bank Indonesia Representative Office consisting of: of 10 Regencies /Cities in Aceh Province.